Primary or secondary chronic functional dizziness: does it make a difference? A DizzyReg study in 356 patients - Habs, Maximilian (J Neurol, 2020)
In 2017, the term “persistent postural-perceptual dizziness” (PPPD) was coined by the Bárány Society, which provided explicit criteria for diagnosis of functional vertigo and dizziness disorders. PPPD can originate secondarily after an organic disorder (s-PPPD) or primarily on its own, in the absence of somatic triggers (p-PPPD). The aim of this database-driven study in 356 patients from a tertiary vertigo center was to describe typical demographic and clinical features in p-PPPD and s-PPPD patients. Patients underwent detailed vestibular testing with neurological and neuro-orthoptic examinations, video-oculography during water caloric stimulation, video head-impulse test, assessment of the subjective visual vertical, and static posturography. All patients answered standardized questionnaires (Dizziness Handicap Inventory, DHI; Vestibular Activities and Participation, VAP; and Euro-Qol-5D-3L). One hundred and ninety-five patients (55%) were categorized as p-PPPD and 162 (45%) as s-PPPD, with female gender slightly predominating (♀:♂ = 56%:44%), particularly in the s-PPPD subgroup (64%). The most common somatic triggers for s-PPPD were benign paroxysmal positional vertigo (27%), and vestibular migraine (24%). Overall, p-PPPD patients were younger than s-PPPD patients (44 vs. 48 years) and showed a bimodal age distribution with an additional early peak in young adults (about 30 years of age) beside a common peak at the age of 50–55. The most sensitive diagnostic tool was posturography, revealing a phobic sway pattern in 50% of cases. s-PPPD patients showed higher handicap and functional impairment in DHI (47 vs. 42) and VAP (9.7 vs. 8.9). There was no difference between both groups in EQ-5D-3L. In p-PPPD, anxiety (20% vs. 10%) and depressive disorders (25% vs. 9%) were more frequent. This retrospective study in a large cohort showed relevant differences between p- and s-PPPD patients in terms of demographic and clinical features, thereby underlining the need for careful syndrome subdivision for further prospective studies.